Strategic crisis communication: navigating digital complexity in aviation case study - Anisa Diniati (Faculty of Communications Science, Dr. Soetomo University, 2025)
Abstract The complexity of crisis communication in the digital era has increased alongside the rapid development of internet technology and social media. This situation has made companies more vulnerable to crises that can significantly impact their reputation and operations. Thus, this study seeks to answer the research question: how can a well-structured and planned issue management strategy help organisations anticipate and address crises in the digital era? This research employed a qualitative approach with an exploratory design to answer this question. In-depth interviews were conducted with senior corporate communication executives and crisis managers from high-reliability organisations (HROs). HROs were selected as the research subjects due to their high-risk operations, which demand highly structured and strategic risk and issue management systems. The findings indicate that proactive issue management strategies based on risk analysis are crucial in mitigating the impact of crises. Furthermore, the results emphasise the importance of integrating digital technologies into communication strategies to enhance the effectiveness of issues and crisis management. This study aims to provide practical recommendations for Public Relations practitioners and offer directions for further research on issue and crisis management in the digital era.